Detection of begomoviruses by peR in weeds and crop plants in and around cotton field infected with cotton leaf curl disease - B.D. AJMERA and V.G. MALATHI*, P.N. SIVALINGAM, K.V. PADMALATHA, B. MANDAL, D. MONGA (Indian Phytopathology, 2007)
A survey was conducted to identify the begomoviruses in weeds and crop plants growing in and around the cotton field infected with cotton leaf curl disease in the major cotton growing areas of Haryana, Punjab and Rajasthan during September, 2003 and 2004, as source of inoculum of the virus causing epidemics in cotton is not yet known. Thirteen weeds and five cultivated crop plants were collected and tested by polymerase chain reaction using universal DNA ~ primers of begomoviruses and primers specific to coat protein gene of begomoviruses infecting cotton (CLCBV-CP).Out of all the plants tested, seven weed species (Croton bonplandianum, Tribulus terrestris, Cucumis sp., Solanum sp., Jatropha curcas, wild sunflower and Xanthium strumarium) and three cultivated crop plants (chilli, mothbean and cluster bean) were positive for DNA ~ amplification indicating the presence of begomoviruses. Two weed species (Tribulus terrestris and Cucumis sp.) were positive for both DNA ~ and CLCBV-CPgene amplification though they were not showing any visible symptoms in the field indicating that they may be probable alternative hosts for CLCBV. During survey it was found that, inspite of high whitefly population (3.0 to 8.4 per plant) the CLCuD incidence was less than 20 percent in this region due to various management practices adopted by the farmers.